Efficacy and safety of Macrolane™ for breast enhancement: A 12-month follow-up study in Asian women. Issue 3 (June 2013) - Yamaguchi, Satoru; Nagumo, Yoshinori; Niwa, Koji
Abstract The demand for breast enhancement has risen substantially over recent years. Stabilised hyaluronic acid of non-animal origin manufactured using NASHA™ technology (Q-Med, Uppsala, Sweden) is an injectable gel, which has increasingly been used as a minimally invasive, non-permanent option for breast enhancement. The aim of this study was to investigate the 12-month efficacy and safety of NASHA gel, when used for breast enhancement in Asian women. Non-pregnant, non-breastfeeding women with small breasts (aged 20–50 years) were recruited into this open, prospective, non-comparative, single-centre study. Subjects received sub-glandular injections of NASHA gel. Efficacy and safety assessments were carried out at follow-up visits (1, 6, and 12 months). Physician and subject assessment of breast improvement was recorded using the Global Esthetic Improvement Scale (GEIS). Ninety-eight subjects of Asian ethnicity were enrolled; 65 subjects completed the 12-month follow-up period. Overall, a median volume of 200 mL (range 80–300 mL) NASHA gel was injected per subject. Following GEIS assessment, 79% of breasts were subject-assessed as improved, much improved, or very much improved 6 months after treatment; 48% of breasts were still considered improved after 12 months. Sub-glandular NASHA gel injection was well tolerated, eliciting no serious adverse events judged to be treatment-related. High rates of aesthetic improvement were observed for at least 6 months after NASHA gel breast enhancement. The minimally invasive injection of NASHA gel provided a treatment option, which was an attractive alternative to permanent breast implants for many women.